The Impact Of Teachers Classroom Management Skills On Learning - Hanan Slamet Waluyo; Nur Amalia (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research aims to determine the teacher's ability to manage classes at SD Negeri 2 Jono by making learning more varied, how teachers understand the character of their students, making class conditions more conducive, maintaining security in the classroom, and analyzing the obstacles that will be experienced by students. teachers in carrying out the class management process and analyzing the impact of class management on student learning. This research is a case study research that is included in a type of qualitative research with data collection carried out using observation techniques, interviews, documentation on teachers and schools at SDN 2 Jono, and seeking references from appropriate related sources. The data analysis technique used is by reducing data, presenting data, and drawing conclusions. The results of this research show that teachers at SD Negeri 2 Jono have implemented their classroom management quite well and kept the classroom more conducive so that it has an impact on students' learning.